Early Hypertransaminasemia after Kidney Transplantation: Significance and Evolution According to Donor Type - Eulàlia Solà-Porta (MDPI AG, 2021)
Early hypertransaminasemia after kidney transplantation (KT) is frequent. It has been associated with the crosstalk produced between the liver and the kidney in ischemia-reperfusion situations. However, the influence of the donor type has not been evaluated. We present a retrospective study analyzing the increase in serum aspartate aminotransferase/alanine aminotransferase (AST/ALT) during the first three months post-KT in 151 recipients who received thymoglobulin as induction therapy, either from brain-death donors (DBD, n = 75), controlled circulatory death donors (cDCD, n = 33), or uncontrolled DCD (uDCD, n = 43). Eighty-five KT recipients from DBD who received basiliximab were included as controls. From KT recipients who received thymoglobulin, 33.6/43.4% presented with an increase in AST/ALT at 72 h post-KT, respectively. Regarding donor type, the percentage of recipients who experienced 72 h post-KT hypertransaminasemia was higher in uDCD group (65.1/83.7% vs. 20.3/26% in DBD and 20.7/27.6% in cDCD, p < 0.001). Within the control group, 9.4/12.9% of patients presented with AST/ALT elevation. One month after transplant, AST/ALT values returned to baseline in all groups. The multivariate analysis showed that uDCD recipients had 6- to 12-fold higher risk of developing early post-KT hypertransaminasemia. Early post-KT hypertransaminasemia is a frequent and transient event related to the kidney donor type, being more frequent in uDCD recipients.